Matching sensitivity to abundance: High resolution immuno-mass spectrometry imaging of lanthanide labels and endogenous elements in the murine brain - Clases, David; De Vega, Raquel Gonzalez; Funke, Sabrina; Lockwood, Thomas E.; Westerhausen, Mika T.; Taudte, Verena; Adlard, Paul A.; Doble, Philip A. (Journal of Analytical Atomic Spectrometry, 2020)
This work introduces a new method for immuno-mass spectrometry imaging via quadrupole-based laser ablation-inductively coupled plasma-mass spectrometry instruments that is matched to the abundance of elements in biological tissues. Manipulation of ion-optics and quadrupole mass filter parameters provided increased transmission of low level high-mass elements, which are typically used as labels for antibodies, at the expense of highly abundant endogenous low-mass elements. Transmission of mid-mass elements such as transition metals was only slightly affected. The implications for mass resolution and background signals are critically discussed and signal to noise ratios and imaging capabilities are compared to those obtained from a standard method. This novel approach resulted in a 6-fold improved signal to noise ratio for lanthanides that are routinely used as elemental labels for antibodies to target protein distributions in biological tissues. This increase in signal intensity, enhanced contrasts, lower limits of detection and the potential to improve spatial resolution contributed to enhanced imaging and trace analyses, as demonstrated by imaging murine brain sections of the hippocampal system and substantia nigra.
CRIS-Team Scopus Importer:2020-04-24